การต่อรองทางเพศสภาพในนิตยสารผู้หญิงและผู้ชาย - มีโชค ราษฎรานุวัต (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The study employed content analysis and in-depth interview to study gender in women s and men’s magazines include factors of magazine organization that affected gender in magazine content. Data were collected from contents of women’s magazines named Preaw and Phooying and men’s magazines named GM, published เท 2001 1 36 issues totally and in-depth interview magazines’ editors. Results of the research are as follow : 1. Women’s magazines accepted femininity in terms of ‘be appearance’ and rejected femininity presented as ‘don’t be successful’. Other femininity characteristics such as ’be housekeeper and presented at home’ 1 were accepted by Preaw while negotiated by Phooying. ’Be weak’, was rejected by Preaw. ’Be sex object’ was accepted by Preaw but rejected by Phooying. For masculinity, women s magazines accepted the characteristic of be successful and ‘be sexual attractive . No rejection was found. 2. Men s magazines accepted almost of femininity and masculinity. There were be sex object and don’t be successful เท femininity terms, and be strong and interested in sport’, be successful’, be aggressive’, be sexual’ and ‘interested in technology and car’ in masculinity terms. However, be weak for femininity as well as don t be housekeeper and presented เท office or outdoor for masculinity were negotiated. 3. Media professional, management system, ownership, advertisers, social and economic contexts, competitors and audience affected gender content in women’s magazines. While media professional, advertisers and audience affected gender content in men s magazines. 4. Women’s magazines accepted some dominant ideologies of gender, they presented some new ideologies showing their negotiated trends. While men s magazines reproduced dominant ideologies of gender, showing their acceptance of dominant gender concept.